Comparison between Variants from Spirometric Test (Vef1) and Six-Minute Walk Test on Patients with Paracoccidioidomycosis after Pulmonary Rehabilitation: Case Reports - Bulla, Henrique Augusto (2009)
The aim of this study was to verify the effectiveness of pulmonary rehabilitation by the exercise tolerance increase through the comparison between the six-minute walk test and the spirometric test. Three male patients presenting the chronic form of Paracoccidioidomycosis were evaluated. They were submitted to evaluations and reevaluations which comprised: patient history, previous respiratory history, dyspnea, cough, spirometry, six-minute walk test, besides thoracic pulmonary reeducation protocols and aerobic training on treadmill three times a week. All the evaluated patients presented positive results after pulmonary reeducation protocol, experiencing in average an increase of 72 meters in the six-minute walk test. However, we must highlight that two patients had a great performance: one of them walked extra 103 meters while comparing to the first test and the other, 85 meters. Just one among the three had a low rating in his performance (only 28 extra meters), which was attributed to the lack of personal dedication and absences during the treatment. After the fulfillment of this study, we can infer that the proposed protocol is effective in the pulmonary rehabilitation of patients with Paracoccidioidomycosis, characterizing the indication of this protocol as advisable.